Pelatihan Aktivitas Sosial pada Lansia untuk Mendukung Kemandirian Kesehatan - Wachidah Yuniartika; Nieldya Nofandrilla; Liana Mangifera; Siti Musalamah; Silvianita Damayanti; Anjani Bharata Ajie (Pusat Penelitian & Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2023)
The purpose of this community service is to increase the independence of the elderly through social activities. This activity was carried out at Posyandu Purbosari 2 and Purbosari 7, Purbayan Village, Sukoharjo regency. Central Java. The target in this activity is the elderly, who actively visit the Purbosari 2 posyandu with 19 elderly people and the Purbosari 7 posyandu with 22 elderly people. The elderly who participated in this activity were all female. This activity will be carried out during May–August 2022. The activity began with a pre-test on the level of independence and knowledge of the elderly, followed by health education, training on making Holahoop Dormants (foot pads), and post-test. The questionnaire used in this devotion uses the Instrumental Activity of Daily Living (IADL) questionnaire consisting of 7 questions and a knowledge questionnaire consisting of 10 questions that have been modified by the devotion team using a guttman scale. The results of the evaluation carried out on the two pre-test posyandu showed good knowledge of 22 people and the post-test good knowledge of 31 people. Level of independence showed independent pre-test results of 26 people and post-test results of 39 people. The suggestion from this community service should be continued by cadres in helping the elderly increase independence by regularly inviting the elderly to make handicrafts and do gymnastics.